2016
DOI: 10.1007/s40279-015-0460-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Overcoming the Sticking Point in Resistance Exercise

Abstract: In the context of resistance training the so-called “sticking point” is commonly understood as the position in a lift in which a disproportionately large increase in the difficulty to continue the lift is experienced. If the lift is taken to the point of momentary muscular failure, the sticking point is usually where the failure occurs. Hence the sticking point is associated with an increased chance of exercise form deterioration or breakdown. Understanding the mechanisms that lead to the occurrence of stickin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 93 publications
1
62
0
Order By: Relevance
“…Several studies that have investigated the bench press have located the SR using this operational definition [ 1 , 4 , 18 , 19 ]. Understanding the SR of maximal lifts is important for strength and conditioning coaches for the avoidance of injury and continued progress in strength adaptations for their athletes [ 20 ]. Gomo and Van Den Tillaar [ 1 ] found that the peak velocity, and local minimum velocity, occurred at a higher position above the chest for a maximal bench press performed with a narrow grip (0.39 ± 0.04 m) by male powerlifters.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies that have investigated the bench press have located the SR using this operational definition [ 1 , 4 , 18 , 19 ]. Understanding the SR of maximal lifts is important for strength and conditioning coaches for the avoidance of injury and continued progress in strength adaptations for their athletes [ 20 ]. Gomo and Van Den Tillaar [ 1 ] found that the peak velocity, and local minimum velocity, occurred at a higher position above the chest for a maximal bench press performed with a narrow grip (0.39 ± 0.04 m) by male powerlifters.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is affected by the “sticking point” of the exercise in question. The sticking point is commonly known as the point in the range-of-motion (ROM) where one experiences a disproportionally large increase in the difficulty to complete the movement ( van den Tillaar and Ettema, 2009 ), and is the performance bottleneck in a resistance exercise ( Kompf and Arandjelovic, 2016 ). In movements where the sticking point occurs in the early phase of the concentric ROM with conventional resistance one might assume that the sticking point occurs later in the movement phase with elastic bands, due to the gradually increasing external resistance, but to our knowledge this has not been experimentally verified.…”
Section: Introductionmentioning
confidence: 99%
“…From the mechanical point of view, the back squat exercise has an ascending characteristic in the strength production, which means that as the concentric phase progresses, greater loads are possible to be lifted 23,24 . Thus, the greatest load that can be lifted in the exercise is determined by the point of least strength, which is known as the "sticking point" and is defined by the point of greatest mechanical disadvantage in the entire ROM of the exercise (~ 90º of knee flexion for BS); after this point, lifting can be completed without major difficulties 25 . The RPE scale is a method used in training sciences mainly to measure the perceived exertion intensity in a given exercise 15,16,19 .…”
Section: Discussionmentioning
confidence: 99%